Pengaruh Media Sosial, Aksebilitas, Fasilitas, Event Pariwisata, dan Daya Tarik Wisata Terhadap Minat Kunjung Wisatawan di Desa Wisata Pagak, Banjarnegara - Lustono Lustono; Kartika Dewi Permatasari (Medikonis, 2022)
ABSTRACT Tourism villages in Indonesia are currently experiencing fairly rapid development. Data from the BPS recorded that there were 1302 tourist villages in 2014, and this number increased to 1734 tourist villages in 2018. The Village Fund is basically to improve people's welfare, by 1) creating jobs, 2) overcoming inequality, and 3) alleviating poverty. In its use, the Village Fund is the authority of the Village, is participatory and through self-management based on village resources is utilized in accordance with the village typology. The purpose of this research is to examine the effect of social media, accessibility, facilities, tourism events, and tourist attractions on the interest of tourists visiting Pagak Tourism Village, Banjarnegara. The type of research in this study is to collect data using a questionnaire. The population used in this study were visitors who came to Pagak Tourism Village, Banjarnegara, using a sample of 100 respondents in this study. The sampling method in this study used a non-probability sampling technique with a purposive sampling method. The results of the research show that Social Media, Accessibility, Facilities, Tourism Events, and Tourist Attractions have a positive effect on Tourist Visiting Interest in Pagak Tourism Village, Banjarnegara. Keywords: Social Media, Accessibility, Facilities, Tourism Events, Tourist Attractions, Tourists' Visiting Interest